THE EFFECT OF COMPENSATION ON LECTURERS PERFORMANCE - Umam, Khoirul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the effect of compensation on lecturer performance at UNUJA. The performance of lecturers in Indonesia, especially at UNUJA, still needs to be improved compared to lecturers at State Universities (PTN). It is suspected that the main factor causing this is compensation, which is still considered low. This type of research uses a quantitative descriptive approach. The sample for this research was lecturers at UNUJA, totalling 33 people. The technique used is Interview and Questionnaire. The data analysis technique uses simple regression analysis with the help of SPSS software. The results of the study show that compensation has a significant effect on the performance of lecturers at UNUJA. The factors that influence lecturer performance are compensation. The results of this study provide input for the improvement of UNUJA in Probolinggo Regency because, if seen from the income of permanent lecturers at UNUJA in Probolinggo Regency, it is still below the average decent income of a lecturer.